Effect of the radiographic contrast material iopamidol on hemostasis: an observational study in thirty cardiac patients - Kilinç, Yurdanur (Elsevier, 2003)
Background: In vitro studies have shown that nonionic radiographic contrast material may induce the generation of thrombin in blood, whereas ionic contrast agents, such as iohexol, do not. However, knowledge of the effects of contrast material on coagulation and fibrinolytic systems in vivo is limited. Objective: This study was designed to assess the effects of the nonionic radiographic contrast material iopamidol on hemostasis in patients undergoing coronary angiography or cardiac catheterization. Methods: Patients aged ≥18 years with chest pain and/or dyspnea who underwent coronary angiography or cardiac catheterization with intra-arterial contrast material were assessed for hemostasis. Blood samples were drawn before and 3 minutes after injection of iopamidol. Complete blood count and coagulation profile (bleeding time, clotting time, clot retraction time, euglobulin lysis time [ELT], prothrombin and partial thromboplastin times, coagulation factor I [CFI] level, and platelet factor 3 [PF-3] availability) were assessed. The natural coagulation inhibitors protein C, protein S, and antithrombin III (AT-III) also were measured. Results: Thirty patients (7 males, 23 females; mean [SD] age, 51.3 [20.2] years; range, 17–79 years) were included in this single-center study. All hematologic variables (hemoglobin, white blood cell count, and platelet count) decreased significantly (P<0.001, P<0.001, and P<0.05, respectively) after administration of iopamidol but remained within normal limits. Mean levels of protein C, protein S, and AT-III did not change significantly after administration of iopamidol. Bleeding time was not changed significantly, and PF-3 availability was prolonged in both groups, but the changes were not statistically significant. Conclusions: In this study population, although hemostasis remained grossly intact after injection of nonionic contrast material, the coagulation system may have been affected by the accelerated consumption of CFI and platelets. The affected variables were platelets, clot retraction time, ELT, and natural coagulation inhibitors (protein C, protein S, and AT-III). Although the natural coagulation inhibitors remained within the normal range, the correlations were found significant. These changes in hemostasis affected the vascular phase. If the vascular compartment, especially the endothelium, remained intact, the infusion of nonionic agents in low concentrations might be safe for angiography and other procedures; however, more studies are needed.